2018
DOI: 10.1016/j.jallcom.2018.07.206
|View full text |Cite
|
Sign up to set email alerts
|

Design and characterization of nano and bimodal structured biodegradable Fe-Mn-Ag alloy with accelerated corrosion rate

Abstract: Researchers in biodegradable metals have been putting efforts to accelerate the corrosion of ironbased biodegradable metals. These include by alloying iron with manganese and noble elements such as silver, but further increase to the corrosion rate is still needed. In this study, a set of bimodal nano/microstructured Fe-30Mn-1Ag alloys was prepared through mechanical alloying and spark plasma sintering. The alloys were characterized and tested for their corrosion behavior in Hanks' solution at 37 o C and for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 52 publications
4
25
0
Order By: Relevance
“…Given that the initial local pH and DO measurements presented in Part I of this work, as well as the changes observed on the microstructure during the experiment, indicated less drastic changes in the local environment over the initial 15 min from immersion (see the initial local results in Part I of this work [ 58 ], which are also consistent with previous reports [ 29 ]), mapping was suitable to follow the evolution of local pH and DO concentration above their surfaces. A representative area was selected to reflect the distribution of local pH and DO concentration ( Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Given that the initial local pH and DO measurements presented in Part I of this work, as well as the changes observed on the microstructure during the experiment, indicated less drastic changes in the local environment over the initial 15 min from immersion (see the initial local results in Part I of this work [ 58 ], which are also consistent with previous reports [ 29 ]), mapping was suitable to follow the evolution of local pH and DO concentration above their surfaces. A representative area was selected to reflect the distribution of local pH and DO concentration ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, a biodegradable Fe–Mn–Ag alloy was designed with accelerated corrosion rate and appropriate antibacterial characteristics. Even though alloying with noble elements was shown to increase the corrosion rate of Fe-base alloy in test media, less significant enhancements have been achieved on their in vivo degradation rate [ 28 , 29 ]. Meanwhile, preferential precipitation of phosphates was observed on the noble phases, which experience higher alkalinisation owing to the oxygen reduction reaction (ORR) occurring on these cathodic sites [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed strategy seemed to be successful when Pd was added to FeMnC steel, with static immersion tests repeatedly showing increased corrosion rates [ 11 , 12 ]. The addition of Ag to FeMn was also successful in a study by Sotoudeh Bagha et al [ 25 ] where just 1 wt.% Ag addition to Fe30Mn led to doubling of the corrosion rate in HBSS. Contrarily, in a recent study by Loffredo et al [ 26 ], the addition of 0.4 wt.% Ag to Fe16Mn0.7C, decreased the corrosion rate.…”
Section: Introductionmentioning
confidence: 98%
“…Decades of early research investigated the potential of Fe‐based stents, where several reports indicated no significant inflammatory responses, neointimal hyperplasia or toxicity, [ 58–60 ] but the resorption period was too slow and hard‐to‐eliminate voluminous corrosion products interfere with neighboring cells and matrix production; [ 55,61 ] however, the corrosion rate and strength can be manipulated through grain size refinement [ 62 ] alloying with Mn (Fe‐35Mn), [ 63 ] and additions of Ag to Fe‐30Mn alloys (Fe‐30Mn‐ X Ag, X = 1 or 3). [ 64 ] Furthermore, a 70 µm strut, nitrided iron stent (0.074 wt% N) exhibited a radial strength of 171 kPa with 2.21% recoil, surpassing the clinical benchmarks of the XIENCE Prime, Absorb GT1, and Magmaris. [ 65 ]…”
Section: Metallic or Polymeric Stents: Mechanical Considerationsmentioning
confidence: 99%